”I need advanced mathematics to pursue the career of my choice” – Norwegian students’ motivations for enrolling in mathematics and plans for post-secondary studies - Pedersen, Ida Friestad (NOMAD Nordic Studies in Mathematics Education, 2013)
Participation in advanced science and mathematics courses in upper secondary school is a gateway to tertiary education and career opportunities in the STEM fields (Science, Technology, Engineering, and Mathematics). The purpose of this study is to investigate Norwegian final-year upper secondary school students’ motivations for choosing to enroll in the most advanced mathematics course offered (3MX), as well as to ascertain their plans for post-secondary education. Since females are underrepresented in mathematics and mathematics-related fields of study, special attention is paid to the gender perspective. The analyses are based on questionnaire data from the large-scale international achievement study TIMSS Advanced, and are framed by the expectancy-value model developed by Eccles and her colleagues (1985). Results show that the subject’s utility value was the primary reason for students’ enrollment in mathematics; that interest in mathematics as a school subject is somewhat more important to the girls than to the boys; and that there are some gender differences in students’ plans for post-secondary studies in the STEM fields.